Emerging Roles of Wnt Ligands in Human Colorectal Cancer - Nie, Xiaobo; Liu, Huiyang; Liu, Lei; Wang, Yan-Dong; Chen, Wei-Dong (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) is the fourth leading cause of cancer death worldwide and constitutive activation of Wnt signaling pathway is universal in most CRC cases. Wnt ligands (Wnts) are secreted glycoproteins and fundamentally essential for the transduction of Wnt signaling pathway. However, the nineteen members of Wnts in humans imply a daunting complexity of Wnt signaling and biological effects, and our understanding of their roles in CRC tumorigenesis is still quite rudimentary. This review will give an overview of the structural characteristics and maturation process of Wnts. Specifically, the expression pattern of all human Wnts in CRC tissues, including Wnt1, Wnt2, Wnt2b, Wnt3, Wnt3a, Wnt4, Wnt5a, Wnt5b, Wnt6, Wnt7a, Wnt7b, Wnt8a, Wnt8b, Wnt9a, Wnt9b, Wnt10a, Wnt10b, Wnt11, Wnt16, and their relationship with the tumorigenesis and progression of CRC will be summarized separately. Despite certain challenges, Wnts-based therapeutics for CRC emerge continuously and some are now in clinical trials. In conclusion, a deeply understanding of Wnts is very helpful for a better management of this disease.